Effects of menaquinone-7 supplementation in patients with aortic valve calcification: study protocol for a randomised controlled trial. Issue 8 (23rd August 2018) - Lindholt, Jes Sanddal; Frandsen, Niels Erik; Fredgart, Maise Høigaard; Øvrehus, Kristian A; Dahl, Jordi Sanchez; Møller, Jacob Eifer; Folkestad, Lars; Urbonaviciene, Grazina; Becker, Søren Warberg; Lambrechtsen, Jess; Auscher, Søren; Hosbond, Susanne; et al.
Abstract : Introduction: Aortic stenosis is a common heart valve disease, and due to the growing elderly population, the prevalence is increasing. The disease is progressive with increasing calcification of the valve cusps. A few attempts with medical preventive treatment have failed; thus, presently, the only effective treatment of aortic stenosis is surgery. This study will examine the effect of menaquinone-7 (MK-7) supplementation on progression of aortic valve calcification (AVC). We hypothesise that MK-7 supplementation will slow down the calcification process. Methods and analysis: In this multicenter and double-blinded, placebo-controlled study, 400 men aged 65–74 years with substantial AVC are randomised (1:1) to treatment with MK-7 (720 µg/day) supplemented by the recommended daily dose of vitamin D (25 µg/day) or placebo treatment (no active treatment) for 2 years. Exclusion criteria are treatment with vitamin K antagonist or coagulation disorders. To evaluate AVC score, a non-contrast CT scan is performed at baseline and repeated after 12 and 24 months of follow-up. Primary outcome is difference in AVC score from baseline to follow-up at 2 years. Intention-to-treat principle is used for all analyses. Ethics and dissemination: There are no reported adverse effects associated with the use of MK-7. The protocol is approved by the Regional Scientific Ethical Committee for Southern Denmark (S-20170059) and the Data Protection Agency (17/19010). It is conducted in accordance with the Declaration of Helsinki. Positive as well as negative findings will be reported. Trial registration number: NCT03243890 .